(untitled) (PROKLA. Journal of Critical Social Science, 2018)
The article describes the development of large listed landlords in Germany (like Vonovia SE) as a specific form of the financialization of housing. Since the end of the 1990s, large stocks of the fordistic and state-socialist housing infrastructures in Germany were sold to Private Equity Funds. After the German recovery from the global financial crisis the fund managers organized the exists through public offerings. Since then a heavy concentration process has taken place that reaches transnational dimensions. The author proposes to call this process “financialized industrialization of corporate housing business”. Integrated into global financial markets and using IT, the public listed real estate companies subjugate trade, facilitation, management, renting and production of housing to standardized financial calculations and automated processes. However, the “real subsumption” of tenants to real estate capital also gives rise to social protests and reclaims.